Applicability and satisfaction profile of two online courses offered by the Construção + project (International Journal of Geoscience, Engineering and Technology, 2020)
The use of digital technologies as a tool for higher education has gained enormous relevance due to the need for the expansion of knowledge beyond the physical boundaries of the institutions. Understanding this context, the extension project "Construção +", developed at the Federal University of Jequitinhonha and Mucuri Valleys stood out in the production of four online courses, offered to society during the period of the pandemic caused by the SARS-CoV-2 virus. The objective of this study was to analyse the applicability of the courses “Photovoltaic System Design Basics” and “Fire Fighting and Prevention Design” and draw a profile of the students' satisfaction. In the registration phase, the interested parties answered a questionnaire with 13 questions related to the profile of the courseist, such as academic training, state that resides, profession and how he knew the project. In the final phase, a satisfaction survey with 34 questions was made available to the students, in order to assess both the applicability of the courses and the technical requirements. From the registration questionnaire, only two questions were selected for analysis and, from the satisfaction survey, 12 questions were selected, totaling 14 questions. From the first questionnaire it can be concluded that, in total terms, more than 80% of the students have completed higher education, in addition 65% of these identified themselves as engineering students. From the satisfaction survey, can be seen that more than 50% of the students considered that the courses contribute to the expansion of learning. Facing the obtained responses from those who managed to complete the courses, it was found that the results were satisfactory, both in relation to the applicability and the satisfaction of the students. Finally, it was verified that the courses offered by the "Constução +" project are a unique alternative for the acquisition of different knowledge, as a complement to face-to-face teaching.